2012
DOI: 10.6060/mhc2012.120571z
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Exchange Dynamics and Temperature Effects upon Formation of Nanocomposites Based on Semiconductor CdSе/ZnS Quantum Dots and Porphyrins: Ensemble and Single Object Measurements

Abstract: Dye molecules with pyridyl side substituents (porphyrins and heterocyclic perylene diimides) coordinatively attached to semiconductor CdSe/ZnS quantum dots (QDs) surface form quasi-stable "QD-Dye" nanocomposites of various geometry in the competition with capping molecules (tri-n-octyl phosphine oxide or long chain amines) exchange. This results in photoluminescence (PL) quenching of the QDs both due to Foerster resonance energy transfer and formation of non-radiative surface states. QD surface is inhomogeneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…In this case, like for multiporphyrin complexes (described above), a controllable formation of "QD-Porphyrin" nanoassemblies have been realized as a surface passivation of CdSe/ZnS ODs by tetrameso-pyridyl substituted porphyrins (free base and/or Cu-complex) in titration experiments. [29,[90][91][92][93][94][95][96][97][98][99] It is well-known from chemical background that the 3d transition metal Zn 2+ ion (of ZnS shell) has empty 3d 10 orbital while heteroatom N-pyr of the porphyrin mesopyridyl ring is a very good e-donor having an unshared electron pair. Thus, in this case a "key-lock" principle is realized via oneor two-fold non-covalent coordination Zn….N-pyr.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this case, like for multiporphyrin complexes (described above), a controllable formation of "QD-Porphyrin" nanoassemblies have been realized as a surface passivation of CdSe/ZnS ODs by tetrameso-pyridyl substituted porphyrins (free base and/or Cu-complex) in titration experiments. [29,[90][91][92][93][94][95][96][97][98][99] It is well-known from chemical background that the 3d transition metal Zn 2+ ion (of ZnS shell) has empty 3d 10 orbital while heteroatom N-pyr of the porphyrin mesopyridyl ring is a very good e-donor having an unshared electron pair. Thus, in this case a "key-lock" principle is realized via oneor two-fold non-covalent coordination Zn….N-pyr.…”
Section: Methodsmentioning
confidence: 99%
“…[97,100,101] We have quantitatively discriminated for the first time, that the major part of the observed PL strong quenching for CdSe/ZnS QD in "QD-Porphyrin" nanoassemblies can be understood in terms of the electron tunneling across the ZnS shell in the conditions of quantum confinement, and the minor part (10-15 %) of the QD PL quenching is caused by Foerster resonance energy transfer (FRET) QD→porphyrin. [90,91,[93][94][95][96][97]123] Instead, the interaction of porphyrin molecules with QD leads to the inhomogeneous surface dynamics for semiconductor QDs and the non-FRET quenching of QD PL in nanoassemblies might be related to few possible reasons: i) depletion of capping ligand TOPO molecules by the respective porphyrin molecules, ii) creation or redistribution of QD surface trap states, iii) low temperature reconstruction of capping ligand layer perturbed by attached porphyrin, etc. Correspondingly, using porphyrins (especially meso-pyridyl substituted H 2 P and CuP) attaching with QD surface, one may tune the electronic states of CdSe/ZnS QD and control luminescent properties of nanoassemblies.…”
Section: Tuning Electronic States Of Cdse/zns Quantum Dot By One Cu-pmentioning
confidence: 98%
See 2 more Smart Citations
“…[75] Using a combination of ensemble and single molecule spectroscopies of "QD-Porphyrin" nanoassemblies, we showed that single functionalized molecules can be considered as extremely sensitive probes for studying the complex interface physics and chemistry and related exciton relaxation processes in QDs. [76][77][78][79][80][81][82][83][84] It was quantitatively shown that the major part of the observed QD photoluminescence (PL) quenching in nanoassemblies is caused by electron tunneling to the QD surface in conditions of quantum confinement, which is influenced by the attachment dynamics of porphyrin molecules. In these nanoassemblies, Foerstertype energy transfer (FRET) QD→dye is often only a small contribution to the PL quenching and is already effectively suppressed in slightly polar solvents.…”
Section: Introductionmentioning
confidence: 99%